Experimental investigation on effect of partial flexibility at low aspect ratio airfoil - Part II: Installation both on suction and pressure surface - Koca Kemal; Genç Mustafa Serdar; Açıkel Halil Hakan (EPJ Web of Conferences, 2022)
In this experimental study, flow over NACA 4412 airfoil with flexible membrane mounted both on suction surface and pressure surface was investigated at Reynolds number of 5x104 and different angles of attack. The smoke-wire visualization method was used for flow visualization to demonstrate flow phenomena as laminar separation bubble (LSB), leading edge separation and tip vortices. A constant temperature anemometer (CTA) was used for measuring flow over the partially flexible airfoil. Concerning the flow visualization, smoke-wire experiment was been conducted at z/c=0.1 and z/c=0.4. Besides, hot-wire experiment by means of CTA was employed to measure flow properties including values of velocity, turbulence statistics and Reynold stress over both uncontrolled and controlled airfoil. The results showed that partially flexible airfoil had several benefits compared with the uncontrolled airfoil. The results for this partially flexible airfoil were mainly lower size of LSB, higher stall angle of attack, ensuring more stable flow characteristics and more aerodynamic performance.